Criticality of physical/social distancing, handwashing, respiratory hygiene and face‐masking during the COVID‐19 pandemic and beyond - Rahimi, Farid (Int J Clin Pract, 2020)
Physical/social distancing, handwashing, respiratory hygiene and face‐masking have been recommended as realistic counterstrategies to control the COVID‐19 pandemic. These strategies have been critical in the fight against the present pandemic in many countries. Here we detail the background to such countermeasures, present some examples in different settings and finally emphasise that they should remain in place worldwide as a cultural and behavioural “new normal” until a vaccine or a decisive treatment for COVID‐19 is developed and made available globally.